Usefulness of Previous Methicillin-resistant Staphylococcus aureus Screening Results in Guiding Empirical Therapy for S Aureus Bacteremia. Issue 4 (2015) - Bai, Anthony D; Burry, Lisa; Showler, Adrienne; Steinberg, Marilyn; Ricciuto, Daniel; Fernandes, Tania; Chiu, Anna; Raybardhan, Sumit; Tomlinson, George A; Bell, Chaim M; Morris, Andrew M
Abstract : BACKGROUND: Staphylococcus aureus bacteremia (SAB) is an important infection. Methicillin-resistant S aureus (MRSA) screening is performed on hospitalized patients for infection control purposes. OBJECTIVE: To assess the usefulness of past MRSA screening for guiding empirical antibiotic therapy for SAB. METHODS: A retrospective cohort study examined consecutive patients with confirmed SAB and previous MRSA screening swab from six academic and community hospitals between 2007 and 2010. Diagnostic test properties were calculated for MRSA screening swab for predicting methicillin resistance of SAB. RESULTS: A total of 799 patients underwent MRSA screening swabs before SAB. Of the 799 patients, 95 (12%) had a positive and 704 (88%) had a negative previous MRSA screening swab. There were 150 (19%) patients with MRSA bacteremia. Overall, previous MRSA screening swabs had a positive likelihood ratio of 33 (95% CI 18 to 60) and a negative likelihood ratio of 0.45 (95% CI 0.37 to 0.54). Diagnostic accuracy differed depending on mode of acquisition (ie, community-acquired, nosocomial or health care-associated infection) (P<0.0001) and hospital (P=0.0002). At best, for health care-associated infection, prior MRSA screening swab had a positive likelihood ratio of 16 (95% CI 9 to 28) and a negative likelihood ratio of 0.27 (95% CI 0.17 to 0.41). CONCLUSIONS: A negative prior MRSA screening swab cannot reliably rule out MRSA bacteremia and should not be used to guide empirical antibiotic therapy for SAB. A positive prior MRSA screening swab greatly increases likelihood of MRSA, necessitating MRSA coverage in empirical antibiotic therapy for SAB.